Labor relations in globalized food - Bonanno, Alessandro; Cavalcanti, Josefa Salete Barbosa (Research in rural sociology and development, 2014)
This book looks at labor in agriculture and food in a global era by studying salient characteristics of the conditions and use of labor in global agri-food. Written by experienced and also emerging scholars, the chapters present a wealth of empirical data and robust theorizations that allow readers to grasp the complexity of this topic.